An overview on the treatment of ballast water in ships. (1st January 2021) - Lakshmi, E.; Priya, M.; Achari, V. Sivanandan
Abstract: Introduction of invasive species through ballast water discharge has been a serious concern with the marine ecosystem. With growing research in the ballast water management, recent studies are being focused on the types of invasive species and physico-chemical parameters discharging into ports. Different treatment and management strategies have been internationally implemented in ships in accordance with ratification of 2004 convention. During designing of new ships ballast water management addresses many innovations by adopting different combination of physical and chemical methods. In depth knowledge on indigenous species of marine ecology is very much important in evaluating invasion of species. Treatment systems used for ballast water are systems adapted for industrial and municipal applications. It is observed that different combination of treatment systems have to be implemented for varied species of organisms present in the ballast tank. Mechanical treatment combined with filtration is found to be the most effective treatment for variable species of organisms and physico-chemical parameters present in the ballast tank. Treatments such as filtration and magnetic separation; filtration and gravity separation; Ultra sound technology, Electrochemical and ozone treatment are found to inactivate 100% of organisms especially zooplanktons and bacteria. A filtration step followed by hydroxyl radical treatment has been found to be the most energy efficient, cost effective, low power consuming and able to inactivate 100% of organisms. Further research should develop a better treatment technology for the ballast water to be D-2 compliant. Highlights: Ballast water has become a very significant problem with the introduction of invasive species. Ballast water exchange plus ballast water treatment is very effective. Among the ballast water treatment, filtration followed by mechanical treatment is effective.. Strong hydroxyl radical treatment shows effectiveness in saving power, space, cost and efficiency. New treatment system like laser treatment can be further researched.